Impact of urban consumers’ food consumption patterns towards food waste - Juhari, Nur Aqilah (2018)
Food waste issues in Malaysia was a growing problem especially in urban area. Population in urban area were the major contributor for food waste generated in Malaysia. Almost 70 percent of food waste are generated in urban area. The changes in the lifestyle of people in urban area might have also changes their behaviour in consumption pattern that leads to food waste. This study aims to determine the impact of urban consumer food consumption pattern toward food waste in urban area. A total of 400 respondents was randomly selected in Klang Valley area consist of Kuala Lumpur, Kajang, Serdang, Putrajaya and Seri Kembangan. Quantitative data is collected by survey method consisting of structured questionnaire and the results were analyzed using descriptive analysis, factor analysis, multiple regression analysis and Chi Square Analysis. The result of the survey through descriptive analysis shows socio-demographic profile of respondents such as gender, age, race, religion, ancestry, district, marital status, education level, occupation and monthly income. Factor analysis have identified three factors that can influence bad behaviour in consumption pattern. These include consumer’s attitude towards food waste reduction, subjective norm and perceived behavioural control. The result from multiple regression analysis discovered that there is significant relationship between Consumer’s attitudes towards food waste reduction with bad behaviour in consumption pattern and there is significant relationship between perceived behavioural controls with bad behaviour in consumption pattern. Only subjective norm were not significantly related with bad behaviour in consumption pattern. The result from multiple regression analysis also suggested that the most influential factor towards bad behaviour in consumption pattern is perceived behavioural control. In addition, the result from chi-square analysis found that there is significant association between bad behaviour in consumption pattern and amount of food wastage.